Influence of day and night temperature and carbon dioxide concentration on growth, yield, and quality of green butterhead and red oakleaf lettuce - Sean T. Tarr; Roberto G. Lopez (PLoS ONE, 2025)
Production of lettuce (Lactuca sativa) within vertical farms is an expanding segment of controlled environment agriculture—precise manipulation of environmental parameters including mean daily temperature (MDT) and carbon dioxide (CO2) concentration enables year-round production, alongside color, yield, and crop size regulation. Our objectives included 1) quantify how MDT and CO2 interact to influence lettuce growth, development, and quality; 2) model lettuce growth under several MDTs and CO2 concentrations. Green butterhead ‘Rex’ and red oakleaf ‘Rouxaï RZ’ seedlings were transplanted into hydroponic tanks under a photosynthetic photon flux density of 300 μmol·m‒2·s‒1 for 17-h·d‒1. CO2 concentrations of 500, 800, or 1200 μmol·mol−1 and day/night and MDT setpoints of 22/15°C (MDT 20°C), 25/18°C (23°C), or 28/21°C (26°C) were maintained within growth chambers. ‘Rex’ fresh mass increased linearly with MDT, increasing by 18% from 20 to 26°C. ‘Rouxaï RZ’ fresh mass increased quadratically with MDT, with a 32% increase from 20 to 23°C, then a 7% increase from 23 to 26°C. Elevating CO2 concentrations from 500 to 800 μmol·mol–1 increased ‘Rouxaï RZ’ and ‘Rex’ fresh mass by 33 and 16%, respectively, while fresh mass did not increase from 800 to 1200 μmol·mol–1. Both cultivars had the greatest dry mass at 800 μmol·mol–1 CO2 across temperatures. At a high MDT, ‘Rouxaï RZ’ foliage color became more light, vibrant, and green, while a low MDT induced darker, grayer, and redder foliage. Tipburn occurred on ‘Rex’ across treatments, while 25% of ‘Rouxaï RZ’ were afflicted at 500 μmol·mol−1 CO2 and 67% at 1200 μmol·mol−1. At the light intensity studied, we recommend growing ‘Rex’ and ‘Rouxaï RZ’ at an 800 μmol·mol−1 CO2 concentration and MDT of 23°C for greatest biomass and leaf number, and slightly redder foliage in ‘Rouxaï RZ’ than at a 26°C MDT.